2021
DOI: 10.31933/dijemss.v2i5.941
|View full text |Cite
|
Sign up to set email alerts
|

Investors' Trust and Risk Perception Using the Investment Platform: A Gender Perspective

Abstract: The development of the technology in financial sector has become opportunities for online trading platform developers, especially in investment. This is a form of encouragement from manual transactions transformation towards digital. The Financial Services Authority stated that of many websites and online investment platforms did not get permission from the them. This will has impacts on the risks that will be carried by the people who use it. On the other hand, as the development of online investment platform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
5
1
Order By: Relevance
“…Men have moderate confidence in investing in this crypto asset, while women have strong confidence, according to research. This result contradicts several previous studies (Astika & Sari, 2019;Kayani et al, 2021;Oliveira et al, 2017;Senkardes & Akadur, 2021;Yang et al, 2021;Zamzami, 2021). Women today are courageous enough to make risky investments.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…Men have moderate confidence in investing in this crypto asset, while women have strong confidence, according to research. This result contradicts several previous studies (Astika & Sari, 2019;Kayani et al, 2021;Oliveira et al, 2017;Senkardes & Akadur, 2021;Yang et al, 2021;Zamzami, 2021). Women today are courageous enough to make risky investments.…”
Section: Discussioncontrasting
confidence: 58%
“…Gender does not moderate the relationship between beliefs and behavioral intentions, according to other studies. (Kayani et al, 2021;Yang et al, 2021;Zamzami, 2021) discovered no difference in men's and women's beliefs about having behavioral intentions in his study. Based on the explanation above, the researcher proposes the following hypothesis:…”
Section: Gender Moderates Trust On Behavioral Intentionsmentioning
confidence: 84%
See 1 more Smart Citation
“…According to Wang, Keller, and Siegrist (as cited by Oliveira et al, 2017), based on gender, women prefer investments in the form of art, antiques, or gold and silver, which have less risk than investments made by men, such as stocks, houses, land, or, in this study, investment in crypto assets. Gender does not moderate the relationship between beliefs and behavioral intentions, according to other studies, which found no differences in men's and women's beliefs about their behavioral intentions (Kayani et al, 2021;Yang et al, 2021;Zamzami, 2021). Based on the explanation above, the researcher proposes the following hypothesis:…”
Section: Gender Moderates Trust On Behavioral Intentions To Invest In...mentioning
confidence: 92%
“…Additionally, it explores participants' psychological dispositions, delineating traits that may render individuals more prone to fraudulent schemes, such as trustfulness, juxtaposed with protective attributes like reflectiveness. Zamzami (2021) explored the usage intensity of online investment platforms during the Covid-19 pandemic, focusing on perceived trust and risk. Employing the clause method, the study conducted online surveys within investor communities in Java Island.…”
Section: Literature Reviewmentioning
confidence: 99%